METODE PENGGALIAN HUKUM PRESPEKTIF ISLAM PROGRESIF ABDULLAH SAEED - febri anto; Zainul Muin Husni (JURNAL HAKAM, 2021)
The religion of Islam is still shackled to an understanding that makes scholars afraid of doing madhzabism. The stagnation of thought has become a big problem faced by scholars. This is what makes Islam in its position is often not in harmony with modern law that is solutive. The sociological approach is no longer in line with the dynamics of society, therefore public trust in religion has been eroded and has resulted in internal Islamic political disputes that consider religion products to be very rigid in providing solutions, hence the writing of this article is more focused on the method brought by Abdullah Saeed in progressive ijtihad method where this method is felt to be very relevant to the times, this paper uses discrete analysis as a method in describing and analyzing the challenges of the progressive Islamic method in carrying out ijtihad and the results of this paper are (1) Abdullah Saeed divides into three groups: the process of interpreting the Koran; textualist group semi-textualist group Contextualist group, (2) Abdullah Saeed's method of ijtihad, who is known as a progressive Muslim, divides into three ijtihad methods which are very well known during the modernization period which he thinks are suitable in influencing the law in the future as long as the law is made: